REFLECTIONS CONCERNING THE CONTENTS OF THE SCHOOL PHYSICAL EDUCATION (Fiep Bulletin - online, 2014)
The objective of this study is to investigate and to reflect about the contents worked in the classes of Physical Education in fundamental schools, of the municipal teaching net of a Pelotas/RS city neighborhood in Brazil. The participants of the research were 15 Physical Education teachers distributed at 7 schools. For the data collection it was used a questionnaire containing closed questions, in which the respondent had to express, in an attitude scale, his/her agreement or disagreement about the subjects presented concerning the contents. The obtained results took to the following final considerations:  starting from this work we have a prospect of the contents of Physical Education at schools, what makes possible other investigation works more deepened on each one of the pointed subjects; To approach the school Physical Education contents  is a complex and a quite wide theme because several components are involved;  When we think in school Physical Education we have to consider the discussions about professional formation, methodology, contents, objectives, sports, gender etc.; The indicators that generated larger consensus were those related to autonomy in the choice of contents and work with contents that please students;  The method of passing the content is important, however a large part of teachers was revealed undecided on his/her methodology. On the worked contents the larger agreement was in relation to the sports and recreation and that they are not specific of each series. It was verified that the sport is still the main activity of the Physical Education school, standing out much more than the other contents, it caused a closed idea in the educational potential development of the discipline;  Objective and content are strongly inter-related in the teacher's practice however the work method is not a clear point for the same ones;  There is an understanding by teachers part that student is plaintiff  party of the teaching-learning process and that their experiences should be respected
Keywords: School; Physical Education; Contents